Um modelo para prover consistência narrativa em Interactive Storytelling - Barros, Leandro Motta (Universidade do Vale do Rio do Sinos, 2007)
Interactive Storytelling (IS) is a research area that aims the development of techniques allowing the creation of interactive systems with emphasis in dramatic and narrative aspects. One approach used in previous work in IS is the use of planning algorithms to define the sequence of events that compose the story. This work intends to investigate techniques that allow to advance towards the solution of three problems found in previous work based on the planning approach for IS: (i) this approach is not inherently narratively consistent; (ii) the user can bring the story to a dead end, in which the planning algorithm cannot find a solution to the story; and (iii) an excessively high workload is put on the stories authors. In order to challenge these problems, three mechanisms that can be added to planning-based IS systems are being proposed: (i) a technique that allows to make the system-generated stories follow a tension arc defined by the story author; (ii) a mechanism that strives to foresee and avoid dead e
Keywords: ambiente virtual inteligente; computação gráfica; computador; interatividade; multimídia; narrativa interativa; jogo; interactive digital entertainment; narratives; planning; interactive storytelling; Ciências Exatas e da Terra